Psychosocial characteristics of the parasuicidal adolescent - Castañeda Chang, Ana María (2002)
48 suicide attempts cases which were reported at Instituto de Salud del Niño de Lima (Child’s Health Institute of Lima) during 1996 to 1999 are studied 88% corresponds to woman and 12% to men cases. Most frequent ages vary between 14 and 17 years old which represent 69% of the registered cases (56%) suicide attempt was caused by disputes with primary support figures or problems in the family group; then 13% accounted for at least one sexual abuse case. Among all the cases only 4% (2 cases) died after caustic soda ingestion, both cases were men. Only a seven-year-old girl case (2%) was found to be a suicide attempt.